Design of Instagram Comic Strips for Learning Media in Elementary School - Iriane, Rara; Saputra, Dhanar Intan Surya; Indarto, Debi; Handani, Sitaresmi Wahyu; Indartono, Kuat (Universitas Muhammadiyah Mataram, 2022)
Information was obtained based on the writer's interviews with the principal at SD Negeri 1 Rawalo elementary school. During the pandemic, students' interest in learning at SD Negeri 1 Rawaloelementary school was relatively low, especially for grade IV students. Especially for Mathematics, Natural Sciences, Social Sciences, Citizenship Education and Indonesian Language. Student interest is low during the pandemic because the learning media is less attractive. The principal wants engagingengaging learning media in the form of comics, such as on Instagram that is easily accessible while studying at home. This media is applied to increase student interest in learning during a pandemic, which must be by the characteristics of the material and learning objectives. Based on this background, the writer was inspired to make a digital comic as a learning medium for elementary school students in grade IV at SD Negeri 1 Rawaloelementary schoolschoolelementary school. The goal is the creation of comic learning media at SD Negeri 1 Rawaloelementary school. The system development method consists of three stages. The pre-production stage, the production stage, and the post-production stage. The pre-production stage, at this stage is a process that includes determining ideas, themes and preparing storyboards. Storyboards are made with two-dimensional images of learning materials. At the production stage, comic character drawings are designed ,given backgrounds and coloring for characters using CorelDraw software. Then at the post production stage, the comic editing process begins using Adobe Photoshop software, starting from setting color balancing, giving shading, merging with comic text, after which the comics are exported and distributed on Instagram. In this research the evaluation of satisfaction learning media was carried out through a questionnaire and the questionnaire was calculated. The results of testing the comic learning media concluded that as many as 79.06%, of and included in the category agree in the application of digital comics as a learning medium for grade IV at SD Negeri 1 Rawaloelementary school. And the post-production stage. The results of testing the comic learning media concluded that as many as 79.06%, of and included in the category agree with the application of digital comics as a learning medium for grade IV at SD Negeri 1 RawaloElementary school. And the post-production stage. The results of testing the comic learning media concluded that as many as 79.06% of and included in the category agree with the application of digital comics as a learning medium for grade IV at SD Negeri 1 RawaloElementary school.